Fast Disinfection of Escherichia coli Bacteria Using Carbon Nanotubes Interaction with Microwave Radiation - Samer M. Al-Hakami; Amjad B. Khalil; Tahar Laoui; Muataz Ali Atieh (Bioinorganic Chemistry and Applications)
Water disinfection has attracted the attention of scientists worldwide due to water scarcity. The most significant challenges are determining how to achieve proper disinfection without producing harmful byproducts obtained usually using conventional chemical disinfectants and developing new point-of-use methods for the removal and inactivation of waterborne pathogens. The removal of contaminants and reuse of the treated water would provide significant reductions in cost, time, liabilities, and labour to the industry and result in improved environmental stewardship. The present study demonstrates a new approach for the removal of Escherichia coli (E. coli) from water using as-produced and modified/functionalized carbon nanotubes (CNTs) with 1-octadecanol groups (C18) under the effect of microwave irradiation. Scanning/transmission electron microscopy, thermogravimetric analysis, and FTIR spectroscopy were used to characterise the morphological/structural and thermal properties of CNTs. The 1-octadecanol (C18) functional group was attached to the surface of CNTs via Fischer esterification. The produced CNTs were tested for their efficiency in destroying the pathogenic bacteria (E. coli) in water with and without the effect of microwave radiation. A low removal rate (3–5%) of (E. coli) bacteria was obtained when CNTs alone were used, indicating that CNTs did not cause bacterial cellular death. When combined with microwave radiation, the unmodified CNTs were able to remove up to 98% of bacteria from water, while a higher removal of bacteria (up to 100%) was achieved when CNTs-C18 was used under the same conditions.